The Use of Modal Particles in The Comic Emil dnd Die Detektive By Isabel Kreitz - Zahrah, Nada Muthia; Santiah, Santiah; Angreany, Femmy (Universitas Negeri Makassar, 2025)
Abstract. Modal particles are interesting to study because they have no meaning when standing alone, but when used in a sentence, they can have meaning depending on the context. Modal particles can help clarify a person's view on an issue, whether it is a sign of agreement or disagreement. Therefore, the focus of this study is the meaning of modal particles in the comic “Emil und die Detektive” by Isabel Kreitz. The theory used is that of modal particles according to Maria Thurmair. This research is a qualitative study using a literature review method with a descriptive approach. The results of this study show a total of 185 modal particles, consisting of 164 non-combined modal particles and 21 combined modal particles. This means that the use of non-combination Modalpartikel accounts for 89%, while the use of combination Modalpartikel is only around 11%. Among the 164 non-combination Modalpartikel, there are 17 types of Modalpartikel in the dialogues of this comic. The Modalpartikel not used are “halt” and “mir.” In the dialogue of the comic “Emil und die Detektive,” many modal particles were found to have dual functions or similar sounds but different meanings. In this comic, there are several types of combined modal particles that do not fall under the categories mentioned by Maria Thurmair, so these modal particles are not counted as combined modal particles. Keywords: Modal particles, Comic, Emil und die Detektive